E-D2CARP: A joint pathand spectrum dicersity based routing protocol with an optimized path selection for corgnitive radio ad hoc networks - Z., CHe-aron; Hassan Abdalla Hashim, Aisha; Hassan, W.H.; Abdullah, K.; Rahman, M.A. (IEEE Communications Society Malaysia Chapter, 2014)
Inteeeactive Multimedia (IMM) applciations such as voice and video conferencing are very important in our learning environment. they offer useful services that benefits its users but these services suffers performance deradation from today's high speed Wireless ocal Area Network (WLAN). hoever, guaranteed Quality of Service (QOS) remains the bottleneck in the network which becomes a great challenge in attempting to improve its performance. this work reviewed manyy approaches and considers mapping QoS class parameters such as quality of Seriive Identifier (QCI), Mazimum Bit Rate (MBR) and Allocation and Retention Priority (ARP) to the upstream and downstream data flowing in the network a an attempt to improve its performance. priority is then given to the QoS bearer packets by associating Differentiated Services COde Point (DSCP). A comprehensive analysis of QoS in different protocols in wireles networks ha been studied. Open issues and research directions have been adressed with a proposed mechanism to enhace the QoS of the wireless network.